(untitled) (Global Journal of Science Frontier Research, 2015)
Indian regional Navigation Satellite system (IRNSS) is going to be an independent, indigenous navigation satellite system fully controlled by India, planned by ISRO. A system was designed of regional navigation satellite constellation, as an alternate to GPS constellation, for providing space based navigation support to various land, sea and air navigation users over the Indian region. The proposed IRNSS constellation consists of 7 satellites (3 in GEO and 4 in inclined GSO with 29 deg inclination). The continuous visibility of GEO and GSO satellites for near-equator regions provides a promising alternative for regional navigation. The Signal In Space (SIS) broadcasts satellite ephemeris in quasi keplarian elements and satellite clock coefficients which forms the primary navigation parameters generated from navigation software located at INC (ISRO Navigation Centre), bylalu, India. The determination of these parameters is performed by two types of technique, batch least square (BLS) and Extended Kalman Filter (EKF).